Safety and efficacy of coronary laser ablation as an adjunctive therapy in percutaneous coronary intervention: a single-centre experience. Issue 3 (12th November 2020) - Mohandes, Mohsen; Fernández, Laura; Rojas, Sergio; Moreno, Cristina; Fuertes, Mónica; Fernández, Francisco; Pernigotti, Alberto; Gonzalez-del-Hoyo, Maribel; Guarinos, Jordi; Sanz, Esther; Bardají, Alfredo
Abstract : Background: Coronary laser is a long-established coadjuvant therapy in interventional cardiology. This study aimed to present our experience regarding the safety and efficacy of laser assistance to percutaneous coronary intervention (PCI) in different scenarios of coronary artery disease. Methods: We used coronary laser as an adjunctive therapy for PCI between May 2014 and March 2020. The safety of laser ablation was evaluated by studying any complication associated with the laser application. Besides, the laser contribution to PCI and 1 year of follow-up for adverse cardiac events was studied. Results: Coronary laser was performed in 81 lesions and 75 patients in different scenarios to assist PCI. The average age was 66 ± 11.7 years and 72 (88.9%) were men. Coronary laser was used in 30 (37%) cases for in-stent-material debulking; 26 (32.1%) in primary angioplasty, 19 (23.4%) in chronic total occlusion and 5 (6.2%) in saphenous vein grafts. Procedural success was achieved in 77 (95.1%) with 1 (1.2%) type III coronary perforation. One year of follow-up for combined adverse cardiac events consisting of death due to any cause, myocardial infarction or target vessel failure showed an event-free rate of 0.82 (95% confidence interval, 0.72–0.91). Conclusions: Our preliminary experience reveals the safety and efficacy of the current modality of coronary laser as a coadjuvant therapy in PCI with a low rate of adverse cardiac events in 1-year of follow-up. Further studies are needed to establish more precisely the contribution of laser application in different contexts of coronary artery disease.